Diffusion and perfusion correlates of the 18F-MISO PET lesion in acute stroke: pilot study - Alawneh, Josef A.; Moustafa, Ramez R.; Marrapu, S. Tulasi; Jensen-Kondering, Ulf; Morris, Rhiannon S.; Jones, P. Simon; Aigbirhio, Franklin I.; Fryer, Tim D.; Carpenter, T. Adrian; Warburton, Elizabeth A.; Baron, Jean-Claude (European journal of nuclear medicine and molecular imaging, 2014)
Purpose Mapping the ischaemic penumbra in acute stroke is of considerable clinical interest. For this purpose, mapping tissue hypoxia with 18 F-misonidazole (FMISO) PET is attractive, and is straightforward compared to 15 O PET. Given the current emphasis on penumbra imaging using diffusion/perfusion MR or CT perfusion, investigating the relationships between FMISO uptake and abnormalities with these modalities is important. Methods According to a prospective design, three patients (age 54–81 years; admission NIH stroke scale scores 16–22) with an anterior circulation stroke and extensive penumbra on CT- or MR-based perfusion imaging successfully completed FMISO PET, diffusion-weighted imaging and MR angiography 6–26 h after stroke onset, and follow-up FLAIR to map the final infarction. All had persistent proximal occlusion and a poor outcome despite thrombolysis. Significant FMISO trapping was defined voxel-wise relative to ten age-matched controls and mapped onto coregistered maps of the penumbra and irreversibly damaged ischaemic core. Results FMISO trapping was present in all patients (volume range 18–119 ml) and overlapped mainly with the penumbra but also with the core in each patient. There was a significant ( p ≤ 0.001) correlation in the expected direction between FMISO uptake and perfusion, with a sharp FMISO uptake bend around the expected penumbra threshold. Conclusion FMISO uptake had the expected overlap with the penumbra and relationship with local perfusion. However, consistent with recent animal data, our study suggests FMISO trapping may not be specific to the penumbra. If confirmed in larger samples, this preliminary finding would have potential implications for the clinical application of FMISO PET in acute ischaemic stroke.